Barriers and facilitators of rehabilitation nursing care for patients with disability in the rehabilitation hospital: A qualitative study - Shirozhan, Shima; Arsalani, Narges; Seyed Bagher Maddah, Sadat; Mohammadi-Shahboulaghi, Farahnaz (Frontiers in Public Health, 2022)
Nurses play a key role in providing rehabilitation care. In this regard, identifying the factors that affect their practice can be useful in planning to improve the quality of rehabilitation nursing care. This study aims to explore the experience of nurses and members of the rehabilitation team about barriers and facilitators of rehabilitation nursing care of patients with disability in the rehabilitation hospital. This qualitative study was conducted in the main public rehabilitation hospital in Tehran, Iran. Eighteen persons including 12 nurses in clinical and managerial positions, an occupational therapist, a physical medicine specialist, a patient, and an informal caregiver participated in this study. Participants were selected based on purposeful sampling. Data were collected through 18 in-depth semi-structured interviews and analyzed based on qualitative content analysis principles. Three themes were derived from the data analysis, which represented Barriers and facilitators related to nurses (specialized knowledge and skills, psychological status, mentoring, professional communication), barriers and facilitators related to the work environment (nurses' performance evaluation, nursing workforce, comprehensive care facilities, workplace design, specialized unit), barriers and facilitators related to patients and caregivers (patient's participation in nursing care, patient adaptation, efficiency of formal caregivers). The experiences of the rehabilitation team shows that not only nurses, but also the environment, patients, and caregivers can affect the provision of care and change the quality of care. Identifying these factors can help managers, researchers, and clinical nurses to facilitate and improve rehabilitation nursing care by modifying the influencing factors.